Effect of Cooking Oil on the Fatty Acid Profile of Beef Sausage Fortified with Edible Deboned Meat Waste - Babatunde O. Alao; Andrew B. Falowo; Elizabeth Bosede Aladejana (International Journal of Food Science)
Application of cooking oil during thermal processing can influence the nutritional qualities of meat products during consumption. This study determined the effect of frying with sunflower and olive oil on the fatty acid profile of sausage fortified with edible meat waste (EMW) as a fat replacer was evaluated. Fresh beef sausages were formulated in ratios of 30% lean meat (LM) and 70% EMW, 50% LM and 50% EMW, and 90% LM and 10% fat (control) and designated as T1, T2, and T3, respectively. The proximate analysis results revealed significant differences (P<0.05) in fat, fat free dry matter (FFDM), and moisture contents across the treatment. Fresh beef sausage fortified with 70% EMW had the highest fat contents (25.7±0.83%) while those fortified with 10% fat (T3) had the highest FFDM (55.85±0.57%) and moisture content (69.15±0.62) compared to other treatments. In addition, among individual saturated fatty acids, beef sausage fortified with 50% meat wastes (T1) revealed significantly higher palmitic acid (31.06±0.13), stearic acid (22.52±0.29), myristic acid (3.84±0.05), and lauric acid (0.04±0.05) and the lowest margaric (0.98±0.02) contents as compared to treatments T2 and T3. Also, beef sausage containing 10% fat showed the lowest (P<0.05) saturated fatty acid (SFA) and higher monounsaturated (MUFA), polyunsaturated fatty acid (PUFA), n-6, n-3, PUFA : SFA, PUFA/MUFA, n-6/n-3, and desaturase indexes (DI) compared to treatments T1 and T2. Frying with sunflower oil significantly increased PUFA, n-6, n-6/n-3, and desaturase indexes and lowered SFA, n-3, and PUFA/SFA compared to frying with olive oil. In relation to raw beef sausage, frying with oil substantially increased the amount of MUFA, PUFA, n-6, and PUFA/SFA but reduced SFA content across the treatments.